Exploring Semester 3 Cadet Perspectives: Unraveling Dynamics in Maritime Education at STIP Jakarta - Marudut Bernadtua Simanjuntak (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
This study delves into the intricacies of the Maritime Education and Training (MET) program at the Maritime Institute Jakarta (STIP Jakarta), focusing on Semester 3 cadets. Adopting a qualitative and descriptive research approach, the research aims to elucidate the perspectives of 240 cadets through the lens of academic self-checked intelligence, professional competences, motivations, and their interconnections. The findings reveal diverse self-checked intelligence profiles across Nautical, Technical, and Port and Shipping Management majors, necessitating a nuanced curriculum tailored to their distinct strengths. English communication emerges as a pivotal professional competence, urging a strategic enhancement of language instruction to equip cadets for effective communication in the global maritime community. Motivations driving cadet dedication encompass familial legacies, a love for the sea, and the pursuit of international exposure. Recognising and nurturing these intrinsic motivators emerges as a crucial element for sustaining cadet engagement. The positive correlation between self-checked intelligence and professional competences underscores the importance of tailored support mechanisms, prompting recommendations for mentorship programs and supplementary resources. Implications for STIP Jakarta include the need for continuous quality improvement through periodic curriculum reviews, fostering a holistic approach that combines technical proficiency with soft skills. The research contributes to the discourse on maritime education, offering a roadmap for institutions to navigate industry dynamics and diverse cadet needs. The findings, discussions, and recommendations collectively enrich the understanding of Semester 3 cadet perspectives, offering actionable insights for educators, administrators, and policymakers to refine and elevate maritime education at STIP Jakarta.